Identification and verification of the pyroptosis-related prognostic signature and its associated regulatory axis in bladder cancer - Tu, Yaofen; Ding, Xiaodi; Mao, Zujie (Frontiers in Cell and Developmental Biology, 2022)
Background: Pyroptosis is an inflammatory form of cell death triggered by certain inflammasomes. Accumulating studies have shown the involvement of pyroptosis in the proliferation, invasion and metastasis and prognosis of cancer. The prognostic value of pyroptosis-related genes (PRGs) and their association with immune infiltration in bladder cancer have not yet been elucidated. Methods: We performed a comprehensive analysis of the prognostic value and immune infiltrates of PRGs in bladder cancer using TCGA dataset. qRT-PCR was also performed to verify our result. Results: Among 33 PRGs, 14 PRGs were upregulated or downregulated in bladder cancer tissue versus normal tissue. We also summarized copy number variations and somatic mutations of PRGs in bladder cancer. By consensus clustering analysis of PRGs with prognostic significance, we divided bladder cancer cohort into two subtypes significantly different prognosis and immune infiltration. Using LASSO Cox regression analysis, A prognostic signature including 6 PRGs was constructed for bladder cancer and the patients could be classified into a low- or high-risk group. Interestingly, this prognostic signature had a favorable performance for predicting the prognosis of bladder cancer patients. Moreover, further analysis demonstrated a significant difference in gender, tumor grade, clinical stage, TNM stage, immunoScore and immune cell infiltration between high- and low-risk group in bladder cancer. We also identified a lncRNA SNHG14/miR-20a-5p/CASP8 regulatory axis in bladder cancer by constructing a ceRNA network. Conclusion: We identified a PRGs-associated prognostic signature associated with the prognosis and immune infiltrates for bladder cancer and targeting pyroptosis may be an alternative approach for therapy. Further vivo and vitro experiments are necessary to verify these results.